Social capital - Field, John. (London ; New York : Routledge, 2008)
'Social Capital' offers an overview of the subject, with explanation of the theoretical underpinnings, the empirical work that has explored its operation & the influence it has had on public policy & practice.
From metaphor to concept -- Networks in use -- A walk on the dark side -- Future tense or present perfect? : social capital in a changing world -- Policy and politics : social capital in the real world.
Includes bibliographical references (p. [169]-188) and index.
Keywords: Social capital (Sociology)